Implementing Instruction with Metaverse: Insights from the TRINGO Concept - Hasan, Hasan; Kuswandi, Dedi; Thaariq, Zahid Zufar At (Jurnal Pendidikan Progresif, 2023)
Implementing Instruction with Metaverse: Insights from the TRINGO Concept. Objective: The purpose of this study is to investigate the implementation of learning using the metaverse, and to link it to the TRINGO approach. Methods: Through a combined meta-synthesis and narrative approach, the results show the positive impact of the metaverse in learning. Findings: The "Ngerti" process with Metaverse creates a holistic learning experience, illustrated by Gemiverse. The "Ngrasa" process shows positive sentiments about the potential of the metaverse to improve the quality of learning. Concrete steps in the "Nglakoni" process, such as addressing privacy and increasing technological accessibility, require positive action and awareness of digital literacy. Conclusion: Overall, this process forms the basis for optimizing the metaverse to enhance understanding, emotional experience, and learning effectiveness. Recommendations for using the metaverse with the TRINGO concept can enrich the educational process in a sustainable way for educators and researchers. Keywords: instructional process, metaverse, tringo, education.DOI: http://dx.doi.org/10.23960/jpp.v13.i3.202327